TARTIL QUR’AN IN THE PERSPECTIVE OF NEUROSCIENCE: INTEGRATION OF TAJWID, TADABBUR, AND NEUROCOGNITION - M Iqbal Nasir; Nurbidayah SA; Nurul Hidayah NR (Ma'had Aly As'adiyah Sengkang, 2025)
This research examines the neurocognitive and psychological effects of Tajwid al-Qur'an, the combined practice of Tajwid (Precise Recitation) and Tadabbur (Deep Contemplation), through a systematic review of neuroscience research. The findings demonstrate that Qur’anic recitation enhances brain function by increasing Alpha Waves (Associated with Relaxation) and Delta Waves (Linked to Deep Focus), while improving memory, emotional regulation, and neural connectivity. Contemplative reflection activates Pre-Frontal Cortex (PFC) functions, boosting critical thinking and spiritual awareness while significantly reducing stress biomarkers. The synergy of these practices provides empirical evidence for the Islamic concept of Qalb (Heart-Mind) as a trainable cognitive-emotional system. These results position Tajwid as both a spiritual practice and evidence-based cognitive therapy, offering groundbreaking insights for Islamic psychology, Qur’anic education methodologies, and spiritually-integrated mental health interventions. The research bridges traditional Islamic knowledge with contemporary neuroscience, suggesting practical applications for enhancing both religious and cognitive development. [Penelitian ini mengkaji efek neurokognitif dan psikologis dari Tajwid al-Qur'an, yaitu praktik gabungan antara Tajwid (Pembacaan yang Tepat) dan Tadabbur (Kontemplasi Mendalam), melalui tinjauan sistematis penelitian neurosains. Temuan penelitian menunjukkan bahwa pembacaan al-Qur'an meningkatkan fungsi otak dengan meningkatkan Gelombang Alpha (Terkait dengan Relaksasi) dan Gelombang Delta (Terkait dengan Fokus Mendalam), sekaligus memperbaiki memori, regulasi emosi, dan konektivitas neural. Refleksi kontemplatif mengaktifkan fungsi Pre-Frontal Cortex (PFC), meningkatkan kemampuan berpikir kritis dan kesadaran spiritual dan pada saat yang bersamaan, secara signifikan mengurangi biomarker stres. Sinergi dari praktik-praktik ini memberikan bukti empiris terhadap konsep Islam tentang Qalb (Hati-Pikiran) sebagai sistem kognitif emosional yang dapat dilatih. Hasil penelitian ini menempatkan Tajwi@d tidak hanya sebagai praktik spiritual tetapi juga terapi kognitif berbasis bukti, yang menawarkan wawasan revolusioner untuk psikologi Islam, metodologi pendidikan al-Qur'an, dan intervensi kesehatan mental yang terintegrasi spiritual. Penelitian ini menjembatani pengetahuan Islam tradisional dengan neurosains kontemporer, serta menyarankan aplikasi praktis untuk meningkatkan perkembangan religius dan kognitif.] Keywords: Tarti@l, Qur’an, Tajwi@d, Tadabbur, Neurocognitive